Re‐endothelialization of rat lung scaffolds through passive, gravity‐driven seeding of segment‐specific pulmonary endothelial cells. (7th May 2017) - Scarritt, Michelle E.; Pashos, Nicholas C.; Motherwell, Jessica M.; Eagle, Zachary R.; Burkett, Brian J.; Gregory, Ashley N.; Mostany, Ricardo; Weiss, Daniel J.; Alvarez, Diego F.; Bunnell, Bruce A.
Abstract: Effective re‐endothelialization is critical for the use of decellularized scaffolds for ex vivo lung engineering. Current approaches yield insufficiently re‐endothelialized scaffolds that haemorrhage and become thrombogenic upon implantation. Herein, gravity‐driven seeding coupled with bioreactor culture facilitated widespread distribution and engraftment of endothelial cells throughout rat lung scaffolds. Initially, human umbilical vein endothelial cells were seeded into the pulmonary artery by either gravity‐driven, variable flow perfusion seeding or pump‐driven, pulsatile flow perfusion seeding. Gravity seeding evenly distributed cells and supported cell survival and re‐lining of the vascular walls while perfusion pump‐driven seeding led to increased cell fragmentation and death. Using gravity seeding, rat pulmonary artery endothelial cells and rat pulmonary vein endothelial cells attached in intermediate and large vessels, while rat pulmonary microvascular endothelial cells deposited mostly in microvessels. Combination seeding of these cells led to positive vascular endothelial cadherin staining. In addition, combination seeding improved barrier function as assessed by serum albumin extravasation; however, leakage was observed in the distal portions of the re‐endothelialized tissue suggesting that recellularization of the alveoli is necessary to complete barrier function of the capillary–alveolar network. Overall, these data indicate that vascular recellularization of rat lung scaffolds is achieved through gravity seeding. Copyright © 2016 John Wiley & Sons, Ltd.